Hadith #2132 - Sunan al-Nasa'i - al-Hakm bin Nafi', Abu al-Yaman Ø§ÙØÙÙ Ø¨Ù ÙØ§ÙØ¹ Ø£Ø¨Ù Ø§ÙÙÙØ§Ù Ø§ÙØÙØµÙ; al-Zuhri Ø§Ø¨Ù Ø´ÙØ§Ø¨ Ø§ÙØ²ÙØ±Ùâ, ÙØÙØ¯ Ø¨Ù ÙØ³ÙÙ; Amr bin Mnswr al-Nsa'iy Ø¹ÙØ±Ù Ø¨Ù ÙÙØµÙØ± Ø§ÙÙØ³Ø§Ø¦Ù Ø£Ø¨Ù Ø³Ø¹ÙØ¯; ibn Abbas; Sa'd bin Ibrahim bin Sa'd Ø³Ø¹Ø¯ Ø¨Ù Ø¥Ø¨Ø±Ø§ÙÙÙ Ø¨Ù Ø³Ø¹Ø¯; Salah bin Kaysan al-Madni ØµØ§ÙØ Ø¨Ù ÙÙØ³Ø§Ù Ø§ÙÙØ¯ÙÙ Ø£Ø¨Ù ÙØÙØ¯; Shu'aib bin Abi Hamza Ø´Ø¹ÙØ¨ Ø¨Ù Ø£Ø¨Ù ØÙØ²Ø©; Ubaidullah bin 'Abdullah bin Abi Thaur Ø¹Ø¨ÙØ¯ Ø§ÙÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø«ÙØ±; Ubaidullah bin Sa'd bin Ibrahim b. Sa'd Ø¹Ø¨ÙØ¯ Ø§ÙÙÙ Ø¨Ù Ø³Ø¹Ø¯ Ø¨Ù Ø¥Ø¨Ø±Ø§ÙÙÙ Ø¨Ù Ø³Ø¹Ø¯ (Sunan al-Nasa'i)
âThe Messenger of Allah said: âD not anticipate the month until you complete the number, or you see the crescent. Then fast, and do not stop fasting until you see the crescent, or your complete thirty days.ââ (Sahih) Al-Hajjaj bin Artah reported it in a Mursal from.
Grade:

Hadith #2607 - Sunan al-Nasa'i - Abdullah bin al-Sa'di; al-Hakm bin Nafi', Abu al-Yaman Ø§ÙØÙÙ Ø¨Ù ÙØ§ÙØ¹ Ø£Ø¨Ù Ø§ÙÙÙØ§Ù Ø§ÙØÙØµÙ; al-Sa'ib bin Yazid bin Akht Namr; al-Zuhri Ø§Ø¨Ù Ø´ÙØ§Ø¨ Ø§ÙØ²ÙØ±Ùâ, ÙØÙØ¯ Ø¨Ù ÙØ³ÙÙ; Amr bin Mnswr al-Nsa'iy Ø¹ÙØ±Ù Ø¨Ù ÙÙØµÙØ± Ø§ÙÙØ³Ø§Ø¦Ù Ø£Ø¨Ù Ø³Ø¹ÙØ¯; Huwaytib bin 'Abdul 'Uzza; Ishaq bin Mansur al-Kausaj Ø¥Ø³ØØ§Ù Ø¨Ù ÙÙØµÙØ± Ø¨Ù Ø¨ÙØ±Ø§Ù - Ø§ÙÙÙØ³Ø¬; Shu'aib bin Abi Hamza Ø´Ø¹ÙØ¨ Ø¨Ù Ø£Ø¨Ù ØÙØ²Ø© (Sunan al-Nasa'i)
âI asked the Messenger of Allah and he gave me, then I asked him and he gave me, then I asked him and he gave me. Then he said: âO Kahim! This wealth is attractive and sweet. Whoever takes it without being greedy, it will be blessed for him, and whoever takes it with avarice, it will not be blessed for him. He is like one who eats and is not satisfied. And the upper hand is better than the lower hand.ââ
Grade:

Hadith #2608 - Sunan al-Nasa'i - al-Hakm bin Nafi', Abu al-Yaman Ø§ÙØÙÙ Ø¨Ù ÙØ§ÙØ¹ Ø£Ø¨Ù Ø§ÙÙÙØ§Ù Ø§ÙØÙØµÙ; al-Zuhri Ø§Ø¨Ù Ø´ÙØ§Ø¨ Ø§ÙØ²ÙØ±Ùâ, ÙØÙØ¯ Ø¨Ù ÙØ³ÙÙ; Amr bin Mnswr al-Nsa'iy Ø¹ÙØ±Ù Ø¨Ù ÙÙØµÙØ± Ø§ÙÙØ³Ø§Ø¦Ù Ø£Ø¨Ù Ø³Ø¹ÙØ¯; ibn Umar; Salim bin 'Abdullah bin 'Umar Ø³Ø§ÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ÙØ± Ø¨Ù Ø§ÙØ®Ø·Ø§Ø¨; Shu'aib bin Abi Hamza Ø´Ø¹ÙØ¨ Ø¨Ù Ø£Ø¨Ù ØÙØ²Ø©; Umar ibn al-Khattab (Sunan al-Nasa'i)
âI asked the Messenger of Allah and he gave me, then I asked him and he gave me. The he said: âO Hakim, this wealth is attractive and sweet. Whoever takes it without being greedy, it will be blessed for him, and whoever takes it with avarice, it will be blessed for him. He is like one who eats and is not satisfied. And the upper hand is better than the lower hand.â I said: âO Messenger of Allah! By the One Who sent you with the truth, I will never ask anyone for anything after you, until
Grade:

Hadith #3223 - Sunan al-Nasa'i - Aisha bint Abi Bakr; al-Hakm bin Nafi', Abu al-Yaman Ø§ÙØÙÙ Ø¨Ù ÙØ§ÙØ¹ Ø£Ø¨Ù Ø§ÙÙÙØ§Ù Ø§ÙØÙØµÙ; al-Zuhri Ø§Ø¨Ù Ø´ÙØ§Ø¨ Ø§ÙØ²ÙØ±Ùâ, ÙØÙØ¯ Ø¨Ù ÙØ³ÙÙ; Imran bin Bakar al-Kula'i Ø¹ÙØ±Ø§Ù Ø¨Ù Ø¨ÙØ§Ø± Ø§ÙÙÙØ§Ø¹Ù; Shu'aib bin Abi Hamza Ø´Ø¹ÙØ¨ Ø¨Ù Ø£Ø¨Ù ØÙØ²Ø©; Urwa ibn al-Zubayr Ø¹Ø±ÙØ© Ø¨Ù Ø§ÙØ²Ø¨ÙØ± (Sunan al-Nasa'i)
It was narrated from Anas that there was a group of the Companions of the Prophet, one of whom said: âI will not marry women.â Another said: âI will not eat meat.â Another said: âI will not sleep on a bed.â Another said: âI will fast and not break my fast.â News of that reached the Messenger of Allah and he praised Allah then said: âWhat is the matter with people who say such and such? But I pray and I sleep, I fast and I break my fast, and I marry women. Whoever turns away f
Grade:

Hadith #3284 - Sunan al-Nasa'i - al-Hakm bin Nafi', Abu al-Yaman Ø§ÙØÙÙ Ø¨Ù ÙØ§ÙØ¹ Ø£Ø¨Ù Ø§ÙÙÙØ§Ù Ø§ÙØÙØµÙ; al-Zuhri Ø§Ø¨Ù Ø´ÙØ§Ø¨ Ø§ÙØ²ÙØ±Ùâ, ÙØÙØ¯ Ø¨Ù ÙØ³ÙÙ; Imran bin Bakar al-Kula'i Ø¹ÙØ±Ø§Ù Ø¨Ù Ø¨ÙØ§Ø± Ø§ÙÙÙØ§Ø¹Ù; Shu'aib bin Abi Hamza Ø´Ø¹ÙØ¨ Ø¨Ù Ø£Ø¨Ù ØÙØ²Ø©; Urwa ibn al-Zubayr Ø¹Ø±ÙØ© Ø¨Ù Ø§ÙØ²Ø¨ÙØ± (Sunan al-Nasa'i)
âInnal-hamda lillahi nahmaduhu wa nastaâinahu, man yahdih Illahu fala mudilla lahu wa man yudlil Illahu fala hadiya lahu, wa ashhadu an la ilaha illallahu (wahdahu lasharika lahu) wa ashhadu anna Muhammadan âabdahu wa rasuluhu. Amma baâd (Praise be to Allah, we seek His help. Whomsoever Allah guides will never be led astray, and whomsoever Allah leaves astray, no one can guide. I bear witness that there is none worthy of worship but Allah (alone with no partners) and I bear witness that
Grade:

Hadith #3746 - Sunan al-Nasa'i - Abu Salama bin 'Abdur Rahman Ø£Ø¨Ù Ø³ÙÙØ© Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø¹ÙÙ; al-Hakm bin Nafi', Abu al-Yaman Ø§ÙØÙÙ Ø¨Ù ÙØ§ÙØ¹ Ø£Ø¨Ù Ø§ÙÙÙØ§Ù Ø§ÙØÙØµÙ; al-Zuhri Ø§Ø¨Ù Ø´ÙØ§Ø¨ Ø§ÙØ²ÙØ±Ùâ, ÙØÙØ¯ Ø¨Ù ÙØ³ÙÙ; Imran bin Bakar al-Kula'i Ø¹ÙØ±Ø§Ù Ø¨Ù Ø¨ÙØ§Ø± Ø§ÙÙÙØ§Ø¹Ù; Jabir ibn 'Abdullah; Shu'aib bin Abi Hamza Ø´Ø¹ÙØ¨ Ø¨Ù Ø£Ø¨Ù ØÙØ²Ø© (Sunan al-Nasa'i)
âHold on to your wealth and do not give it on the basis of âUmra. For whoever is given something on the basis of âUmra for the rest of his life, it belongs to him for the rest of his life and after his death.â
Grade:

Hadith #3945 - Sunan al-Nasa'i - Aisha bint Abi Bakr; al-Hakm bin Nafi', Abu al-Yaman Ø§ÙØÙÙ Ø¨Ù ÙØ§ÙØ¹ Ø£Ø¨Ù Ø§ÙÙÙØ§Ù Ø§ÙØÙØµÙ; al-Zuhri Ø§Ø¨Ù Ø´ÙØ§Ø¨ Ø§ÙØ²ÙØ±Ùâ, ÙØÙØ¯ Ø¨Ù ÙØ³ÙÙ; Imran bin Bakar al-Kula'i Ø¹ÙØ±Ø§Ù Ø¨Ù Ø¨ÙØ§Ø± Ø§ÙÙÙØ§Ø¹Ù; Shu'aib bin Abi Hamza Ø´Ø¹ÙØ¨ Ø¨Ù Ø£Ø¨Ù ØÙØ²Ø© (Sunan al-Nasa'i)
âI do not know that Shuraih ever ruled on Mudarabah disputes except in two ways. He would say to the Mudarib (the one who contributed his labor to the partnership): âYou must provide proof that a calamity befell you so that you may be excused.â Or he would say to the one who invested his money in the partnership: âYou must provide proof that your trustee betrayed his trust, otherwise his oath sworn by Allah that he did not betray you is sufficient.'â
Grade:

Hadith #3954 - Sunan al-Nasa'i - Abu Salama bin 'Abdur Rahman Ø£Ø¨Ù Ø³ÙÙØ© Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø¹ÙÙ; Aisha bint Abi Bakr; al-Hakm bin Nafi', Abu al-Yaman Ø§ÙØÙÙ Ø¨Ù ÙØ§ÙØ¹ Ø£Ø¨Ù Ø§ÙÙÙØ§Ù Ø§ÙØÙØµÙ; al-Zuhri Ø§Ø¨Ù Ø´ÙØ§Ø¨ Ø§ÙØ²ÙØ±Ùâ, ÙØÙØ¯ Ø¨Ù ÙØ³ÙÙ; Amr bin Mnswr al-Nsa'iy Ø¹ÙØ±Ù Ø¨Ù ÙÙØµÙØ± Ø§ÙÙØ³Ø§Ø¦Ù Ø£Ø¨Ù Ø³Ø¹ÙØ¯; Shu'aib bin Abi Hamza Ø´Ø¹ÙØ¨ Ø¨Ù Ø£Ø¨Ù ØÙØ²Ø© (Sunan al-Nasa'i)
âThe wives of the Prophet sent Fatimah, the daughter of the Messenger of Allah, to the Messenger of Allah. She asked permission to enter when he was lying with me under my cover. He gave her permission to enter, and she said: âO Messenger of Allah, your wives have sent me to you to ask you to be equitable with regard to the matter of the daughter of Abu Quhafah.â I (âAishah) kept quiet and the Messenger of Allah said to her: âO my daughter! Do you not love the one whom I love?â She s
Grade:

Hadith #2470 - Sunan Abi Dawud - al-Hakm bin Nafi', Abu al-Yaman Ø§ÙØÙÙ Ø¨Ù ÙØ§ÙØ¹ Ø£Ø¨Ù Ø§ÙÙÙØ§Ù Ø§ÙØÙØµÙ; Muhammad bin Yahya bin Hiban ÙØÙØ¯ Ø¨Ù ÙØÙÙ Ø¨Ù ØØ¨Ø§Ù; Shu'aib bin Abi Hamza Ø´Ø¹ÙØ¨ Ø¨Ù Ø£Ø¨Ù ØÙØ²Ø© (Sunan Abi Dawud)
When the Messenger of Allah (ï·º) was observing Iâtikaf (in the mosque), I would come to him to visit him. I had a talk with him and then stood up. I then returned and he (the Prophet) also stood up to accompany me (to my house). Her dwelling place was in the house of Usamah b. Zaid. Two men from the Ansar (helpers) passed (by him at the moment). When they saw the Prophet (ï·º), they walked quickly. The Prophet (ï·º) said: Be at ease, she is Safiyyah daughter of Huyayy. They said: Be glory to
Grade: Sahih

Hadith #2660 - Sunan Abi Dawud - al-Hakm bin Nafi', Abu al-Yaman Ø§ÙØÙÙ Ø¨Ù ÙØ§ÙØ¹ Ø£Ø¨Ù Ø§ÙÙÙØ§Ù Ø§ÙØÙØµÙ; al-Zuhri Ø§Ø¨Ù Ø´ÙØ§Ø¨ Ø§ÙØ²ÙØ±Ùâ, ÙØÙØ¯ Ø¨Ù ÙØ³ÙÙ; Amr bin Abi Sufyan Ø¹ÙØ±Ù Ø¨Ù Ø£Ø¨Ù Ø³ÙÙØ§Ù Ø¨Ù Ø£Ø³ÙØ¯; Shu'aib bin Abi Hamza Ø´Ø¹ÙØ¨ Ø¨Ù Ø£Ø¨Ù ØÙØ²Ø© (Sunan Abi Dawud)
Abu Hurairah said âThe Prophet (ï·º) sent ten persons (on an expedition) and appointed âAsim bin Thabit their commander. About one hundred men of Hudhail who were archers came out to (attack) them. When âAsim felt their presence, they took cover in a hillock. They aid to them âCome down and surrender and we make a covenant and pact with you that we shall not kill any of youâ. âAsim said âI do not come to the protection of a disbeliever. Then they shot them with arrows and killed â
Grade: Sahih

Hadith #2740 - Sunan Abi Dawud - Abd al-Whab bin Njd'h Ø¹Ø¨Ø¯ Ø§ÙÙÙØ§Ø¨ Ø¨Ù ÙØ¬Ø¯Ø©; al-Hakm bin Nafi', Abu al-Yaman Ø§ÙØÙÙ Ø¨Ù ÙØ§ÙØ¹ Ø£Ø¨Ù Ø§ÙÙÙØ§Ù Ø§ÙØÙØµÙ; al-Walid bin Muslim al-Quraishi Ø§ÙÙÙÙØ¯ Ø¨Ù ÙØ³ÙÙ Ø§ÙÙØ±Ø´Ù; ibn Umar; Mubashir bin Isma'i ÙØ¨Ø´Ø± Ø¨Ù Ø¥Ø³ÙØ§Ø¹ÙÙ - Ø£Ø¨Ù Ø¥Ø³ÙØ§Ø¹ÙÙ Ø§ÙÙÙØ¨Ù; Muhammad bin Awf bin Sufyan ÙØÙØ¯ Ø¨Ù Ø¹ÙÙ Ø¨Ù Ø³ÙÙØ§Ù Ø§ÙØ·Ø§Ø¦Ù; Nafie' ÙØ§ÙØ¹ ÙÙÙÙ Ø§Ø¨Ù Ø¹ÙØ±; Shu'aib bin Abi Hamza Ø´Ø¹ÙØ¨ Ø¨Ù Ø£Ø¨Ù ØÙØ²Ø© (Sunan Abi Dawud)
Musâab bin Saâd reported on the authority of his father (Saâad bin Abi Waqqas) âI brought a sword to the Prophet(ï·º) on the day of the Badr and I said (to him) Apostle of Allaah(ï·º) , Allaah has healed up my breast from the enemy today, so give me this sword. He said âThis sword is neither mine nor yours. I then went away saying âtoday this will be given to a man who has not been put to trial like me. Meanwhile a messenger and came to me and said âRespond, I thought something was
Grade: Hasan Sahih

Hadith #2999 - Sunan Abi Dawud - Abdullah bin Ka'b bin Malik b. Abi Ka'b; Abdur Rahman bin 'Abdullah bin Ka'b Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù ÙØ¹Ø¨ Ø¨Ù ÙØ§ÙÙ; al-Hakm bin Nafi', Abu al-Yaman Ø§ÙØÙÙ Ø¨Ù ÙØ§ÙØ¹ Ø£Ø¨Ù Ø§ÙÙÙØ§Ù Ø§ÙØÙØµÙ; al-Zuhri Ø§Ø¨Ù Ø´ÙØ§Ø¨ Ø§ÙØ²ÙØ±Ùâ, ÙØÙØ¯ Ø¨Ù ÙØ³ÙÙ; Muhammad bin Yahya bin Hiban ÙØÙØ¯ Ø¨Ù ÙØÙÙ Ø¨Ù ØØ¨Ø§Ù; Shu'aib bin Abi Hamza Ø´Ø¹ÙØ¨ Ø¨Ù Ø£Ø¨Ù ØÙØ²Ø© (Sunan Abi Dawud)
We were at Mirbad. A man with dishevelled hair and holding a piece of red skin in his hand came. We said: You appear to be a bedouin. He said: Yes. We said: Give us this piece of skin in your hand. He then gave it to us and we read it. It contained the text: âFrom Muhammad, Messenger of Allah (ï·º), to Banu Zuhayr ibn Uqaysh. If you bear witness that there is no god but Allah, and that Muhammad is the Messenger of Allah, offer prayer, pay zakat, pay the fifth from the booty, and the portion of
Grade: Sahih

Hadith #3606 - Sunan Abi Dawud - al-Hakm bin Nafi', Abu al-Yaman Ø§ÙØÙÙ Ø¨Ù ÙØ§ÙØ¹ Ø£Ø¨Ù Ø§ÙÙÙØ§Ù Ø§ÙØÙØµÙ; al-Zuhri Ø§Ø¨Ù Ø´ÙØ§Ø¨ Ø§ÙØ²ÙØ±Ùâ, ÙØÙØ¯ Ø¨Ù ÙØ³ÙÙ; Ammara bin Khuzayma bin Thabit Ø¹ÙØ§Ø±Ø© Ø¨Ù Ø®Ø²ÙÙØ© Ø¨Ù Ø«Ø§Ø¨Øª Ø§ÙØ£ÙØµØ§Ø±Ù Ø§ÙØ£ÙØ³Ù; Muhammad bin Yahya bin Hiban ÙØÙØ¯ Ø¨Ù ÙØÙÙ Ø¨Ù ØØ¨Ø§Ù; Shu'aib bin Abi Hamza Ø´Ø¹ÙØ¨ Ø¨Ù Ø£Ø¨Ù ØÙØ²Ø© (Sunan Abi Dawud)
A man from Banu Sahm went out with Tamim ad-Dari and Adi ibn Baddaâ. The man of Banu Sahm died in the land where no Muslim was present. When they returned with his inheritance, they (the heirs) did not find a silver cup with lines of gold (in his property). The Messenger of Allah (ï·º) administered on oath to them. The cup was then found (with someone) at Mecca. They said: We have bought it from Tamim and Adi. Then two men from the heirs of the man of Banu Sahm got up and swore saying: Our wit
Grade: Sahih

Hadith #3795 - Sunan Abi Dawud - Abdur Rahman bin Shabal al-Ansari; Abu Rashid al-Hbrany Ø£Ø¨Ù Ø±Ø§Ø´Ø¯ Ø§ÙØØ¨Ø±Ø§ÙÙ; al-Hakm bin Nafi', Abu al-Yaman Ø§ÙØÙÙ Ø¨Ù ÙØ§ÙØ¹ Ø£Ø¨Ù Ø§ÙÙÙØ§Ù Ø§ÙØÙØµÙ; Damdam bin Zar'ah Ø¶ÙØ¶Ù Ø¨Ù Ø²Ø±Ø¹Ø© Ø¨Ù Ø«ÙØ¨; Muhammad bin Awf bin Sufyan ÙØÙØ¯ Ø¨Ù Ø¹ÙÙ Ø¨Ù Ø³ÙÙØ§Ù Ø§ÙØ·Ø§Ø¦Ù; Sharyh bin 'Ubaid Ø´Ø±ÙØ Ø¨Ù Ø¹Ø¨ÙØ¯ Ø¨Ù Ø´Ø±ÙØ (Sunan Abi Dawud)
We were in an army with the Messenger of Allah (ï·º). We got some lizards. I roasted one lizard and brought it to the Messenger of Allah (ï·º) and placed it before him. He took a stick and counted its fingers. He then said: A group from the children of Israâil was transformed into an animal of the land, and I do not know which animal it was. He did not eat it nor did he forbid (its eating).
Grade: Sahih

Hadith #4874 - Sunan Abi Dawud - al-Hakm bin Nafi', Abu al-Yaman Ø§ÙØÙÙ Ø¨Ù ÙØ§ÙØ¹ Ø£Ø¨Ù Ø§ÙÙÙØ§Ù Ø§ÙØÙØµÙ; Muhammad bin Awf bin Sufyan ÙØÙØ¯ Ø¨Ù Ø¹ÙÙ Ø¨Ù Ø³ÙÙØ§Ù Ø§ÙØ·Ø§Ø¦Ù; Nawful bin Masahiq bin 'Abdullah ÙÙÙÙ Ø¨Ù ÙØ³Ø§ØÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ; Sa'id bin Zayd; Shu'aib bin Abi Hamza Ø´Ø¹ÙØ¨ Ø¨Ù Ø£Ø¨Ù ØÙØ²Ø© (Sunan Abi Dawud)
The Messenger of Allah (ï·º) was asked: Messenger of Allah! What is back-biting? He replied: It is saying something about your brother which he would dislike. He was asked again: Tell me how the matter stands if what I say about my brother is true? He replied: If what you say of him is true, you have slandered him, and if what you say of him is not true, you have reviled him.
Grade: Sahih

Hadith #5270 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi Ø¹Ø¨Ø¯ Ø§ÙØ¹Ø²ÙØ² Ø¨Ù ÙØÙØ¯ Ø§ÙØ¯Ø±Ø§ÙØ±Ø¯Ù; Abdullah bin Muslima al-Qa'nabi Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù ÙØ³ÙÙØ© Ø¨Ù ÙØ¹ÙØ¨ Ø§ÙÙØ¹ÙØ¨Ù; Abu Usayd Malik bin Rabi'a; al-Hakm bin Nafi', Abu al-Yaman Ø§ÙØÙÙ Ø¨Ù ÙØ§ÙØ¹ Ø£Ø¨Ù Ø§ÙÙÙØ§Ù Ø§ÙØÙØµÙ; Hamza bin Abi Usayd al-Sa'idi; Shdad bin Abi 'Amr Ø´Ø¯Ø§Ø¯ Ø¨Ù Ø£Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØÙØ§Ø³ (Sunan Abi Dawud)
The Messenger of Allah (ï·º) prohibited throwing pebbles (in sport) saying : game is not caught by such means. Neither is an enemy injured, but it may sometimes put out an eye or break a tooth.
Grade: Sahih

Hadith #2391 - Jami' al-Tirmidhi - Abu Hurairah; al-Hakm bin Nafi', Abu al-Yaman Ø§ÙØÙÙ Ø¨Ù ÙØ§ÙØ¹ Ø£Ø¨Ù Ø§ÙÙÙØ§Ù Ø§ÙØÙØµÙ; ibn Abbas; Ibrahim bin Sa'id al-Juhari Ø¥Ø¨Ø±Ø§ÙÙÙ Ø¨Ù Ø³Ø¹ÙØ¯ Ø§ÙØ¬ÙÙØ±Ù; Nafi' bin Jubayr bin Mut'im ÙØ§ÙØ¹ Ø¨Ù Ø¬Ø¨ÙØ± Ø¨Ù ÙØ·Ø¹Ù; Shu'aib bin Abi Hamza Ø´Ø¹ÙØ¨ Ø¨Ù Ø£Ø¨Ù ØÙØ²Ø© (Jami' al-Tirmidhi)
âWhen one of you loves his brother,then let him inform him of it.â
Grade:

Hadith #2077 - Sunan Ibn Majah - al-Hakm bin Nafi', Abu al-Yaman Ø§ÙØÙÙ Ø¨Ù ÙØ§ÙØ¹ Ø£Ø¨Ù Ø§ÙÙÙØ§Ù Ø§ÙØÙØµÙ; al-Miswar bin Makhrama bin Nawfal; al-Zuhri Ø§Ø¨Ù Ø´ÙØ§Ø¨ Ø§ÙØ²ÙØ±Ùâ, ÙØÙØ¯ Ø¨Ù ÙØ³ÙÙ; Ali bin al-Husain bin 'Ali Ø¹ÙÙ Ø¨Ù Ø§ÙØØ³ÙÙ Ø¨Ù Ø¹ÙÙ - Ø²ÙÙ Ø§ÙØ¹Ø§Ø¨Ø¯ÙÙ; Muhammad bin Yahya bin Hiban ÙØÙØ¯ Ø¨Ù ÙØÙÙ Ø¨Ù ØØ¨Ø§Ù; Shu'aib bin Abi Hamza Ø´Ø¹ÙØ¨ Ø¨Ù Ø£Ø¨Ù ØÙØ²Ø© (Sunan Ibn Majah)
some people referred a dispute to the Prophet (ï·º) about a hut, so that he could judge between them. He sent Hudhaifah to judge between them, and he ruled in favor of those who had the rope (with which the hut was blinded together). When he went back to the Prophet (ï·º) he told him (what he had done) and he said: âYou did the right thing, and you did well.â
Grade: